Description of a new species of the genus Rhopalovalva Kuznetzov (Tortricidae, Olethreutinae) from Japan - Nasu, Yoshitsugu (Zootaxa, 2021)
Rhopalovalva chidorinoki Nasu, sp. nov. is described from Japan, with the photographs of the adult and genitalia. The diagnostic characters of the new species are given with comparison with the allied species, R. exartemana (Kennel, 1901).